Shotgun metagenomics reveals hydrocarbon-degradation potential in vehicle-wash drainage sludge and GC-MS validation of n-alkane removal by an indigenous Bacillus amyloliquefaciens in wastewater microcosms - Ngo , Cao Cuong; Nguyen, Thi Kim Thanh; Tran, Thi Thanh Thuy; Do, Thi Tuyen (Journal of Degraded and Mining Lands Management, 2026)
Vehicle-wash wastewater can contain petroleum-derived residues that accumulate in drainage sludge and pose persistent environmental risks. In this study, shotgun metagenomics of drainage sludge from a vehicle-wash ditch were combined with isolate level validation to assess indigenous hydrocarbon biodegradation potential. Taxonomic profiling revealed a community dominated by Proteobacteria (notably Gammaproteobacteria), while Bacillus was detected only at low relative abundance at the genus level. Functional annotation indicated strong genetic potential for alkane activation and downstream processing, together with multiple enzymes associated with aromatic?ring transformation. To link this community-level potential with experimentally verifiable activity, an indigenous isolate recovered from the sludge was identified as Bacillus amyloliquefaciens MD3.3 based on 16S rRNA gene sequencing (GenBank: PV550465). In microcosms prepared with wastewater from the same drainage source, GC-MS analysis demonstrated marked attenuation of mineral oil n-alkanes over 0-7-14 days. ?n?alkanes decreased from 185,346.63 ± 11,120.80 µg/L at Day 0 to 21,498.48 ± 3,224.77 µg/L at Day 7 and 260.82 ± 52.16 µg/L at Day 14, corresponding to 88.44 ± 1.05% and 99.86 ± 0.02% removal, respectively (n = 3). In contrast, abiotic sterilized controls showed only minor non-biological losses (4.23 ± 3.54% and 5.97 ± 0.75% removal at Days 7 and 14). Collectively, these results support the feasibility of site-relevant bioremediation for vehicle-wash wastewater.